Anti-Photoaging Effect of Jawoongo via Regulating Nrf2/ARE and TGF-β/Smad Signaling in In Vitro Photoaging Model - Hongyong Kim; Qiwen Zheng; Sarang Oh; Shengdao Zheng; Myeongju Kim; Tae-Hoo Yi (Applied Sciences, 2023)
Jawoongo is a traditional prescription used widely in East Asia for external applications and is effective for burns, sunburn, wounds, and symptoms of dryness in skin disease. This study was established to examine how Jawoongo treatment affects the photodamage of HaCaT cells caused by ultraviolet B (UVB) irradiation and explore its possible anti-photoaging mechanisms from the perspective of the associated signaling pathways. An in vitro photoaging model was established by irradiating HaCaT with UVB, and the expression of photodamage markers such as matrix metalloproteinases (MMPs) and reactive oxygen species (ROS) was assessed by enzyme-linked immunosorbent assay (ELISA), FACs, and RT-PCR. Western blotting was also used to ascertain the expression levels of the TGF-β/Smad and nuclear erythroid 2-related factor (Nrf2)/antioxidant response element (ARE) signaling pathways. The findings of this study showed that the increased production of ROS, MMP-1, and MMP-3 due to UVB irradiation was reduced by Jawoongo. In addition, the Nrf2/ARE and TGF-β/Smad pathways were upregulated by Jawoongo, while it reduced phosphorylation activation of the mitogen-activated protein kinase (MAPK)/activator protein 1 (AP-1) pathway. This study shows that Jawoongo regulates the Nrf2/ARE and TGF-β/Smad signaling pathways in UVB-irradiated HaCaT cells, highlighting its potential to protect against and repair skin photodamage.